Collaboration between NGOs and village governments in the conservation of customary forests in the Datuk Sinaro Putih customary forest, Bungo Regency, Jambi - Ridwan; Siti Maryam; Nanda Kurniadi (International Journal of Qualitative Research, 2026)
This study aims to obtain a clear picture of the forms of collaboration and identify the barriers and challenges experienced by the Non-Governmental Organization (NGO) CAPPA, the Ecological Justice Foundation, and the village government in preserving the Datuk Sinaro Putih Customary Forest in Batu Kerbau Hamlet, Pelepat District, Bungo Regency. Based on the description, identification, and analysis of the research problem, this study used a descriptive qualitative approach. Data were collected through desk research, field research, observation, interviews, and documentation. The Datuk Sinaro Putih Indigenous Community is a community that is wise in protecting its forest and environment. They possess local wisdom values in preserving the natural environment, including customary philosophy and rules as guidelines for forest and environmental protection. The establishment of customary forests and forbidden areas is an effort to preserve the environment and protect the remaining forest. Furthermore, customary oaths are held to maintain community unity in protecting the natural environment. Inhibiting factors include limited human resource capacity, individual/group interests within the institution, and weak coordination and interaction between NGOs and related institutions (stakeholders).